Osteogenesis Imperfecta Due to Combined Heterozygous Mutations in Both COL1A1 and COL1A2, Coexisting With Pituitary Stalk Interruption Syndrome - Wang, Dongdong; Zhang, Mengmeng; Guan, Haixia; Wang, Xiaoli (Frontiers in Endocrinology, 2019)
Osteogenesis imperfecta (OI) is a hereditary connective tissue disorder, characterized by reduced bone content, fractures and skeletal malformation due to abnormal synthesis or dysfunction of type I collagen protein. Pituitary stalk interruption syndrome (PSIS) is usually associated with environmental and hereditary factors. Here, we report a rare case of OI and PSIS co-occurrence. A 19-year-old male patient sought treatment for growth delay and absent secondary sexual characteristics. Hormone measurements indicated the presence of hypopituitarism (secondary hypothyroidism, growth hormone deficiency, ACTH-cortisol hormone deficiency, hypogonadotropic hypogonadism). Pituitary magnetic resonance imaging indicated reduced morphology of the anterior lobe, absence of the pituitary stalk, and ectopic displacement of the posterior lobe to the infundibulum, supporting a diagnosis of PSIS. In addition, the patient, his monozygotic twin brother (no evidence of PSIS), and their mother all presented blue sclera and susceptibility to bone fractures before adulthood. Next-generation sequencing demonstrated that the family had compound heterozygous mutations in COL1A1 and COL1A2, with no known mutations related to PSIS, pituitary hormone deficiency (PHD), or holoprosencephaly (HPE). The mother experienced breech and natural delivery of the patient and his brother, respectively. Thus, we deduced that the patient's PSIS might have resulted from breech delivery. Although we cannot exclude the possibility that the proband might have an undetected genetic abnormality causing PSIS or increasing his susceptibility to damage to the hypothalamic-pituitary region due to the limitation of exome sequencing, this rare case suggests that breech delivery in the newborn with OI might be related to PSIS.